2018
DOI: 10.1016/j.cej.2018.07.216
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 3-nitro-1,2,4-trizole-5-one (NTO) in wastewater with UV/H2O2 oxidation

Abstract: Insensitive Munition (IM) formulations contain 3-nitro-1,2,4-trizole-5-one (NTO), an energetic compound with the highest aqueous solubility (16 g L-1) among all IM explosives, including 2, 4-dinitroanisole (DNAN) and 1-nitroguanidine (NQ); as a result wastewater streams from IM processing facilities can be highly contaminated and potentially toxic. The removal of energetic compounds from wastewater streams prior to their discharge in the environment is imperative, and new technology must be developed to effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The solubility of IHEM-1 in water is limited and it is even lower in organic solvents, such as DMSO, MeOH, EtOH, acetonitrile (MeCN), dimethylformamide (DMF), and ethyl acetate (EA). Its solubility was determined to be 6.75 mg in 100 mL of water at room temperature (25 °C), and even at 100 °C, its solubility is only 28.1 mg in 100 mL, which is significantly lower than those of ICM-102 and NTO (220 and 1600 mg in 100 mL of water at room temperature, respectively), , This low solubility may arise from the abundance of short intermolecular H-bonds. The same is true for compound 1b .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The solubility of IHEM-1 in water is limited and it is even lower in organic solvents, such as DMSO, MeOH, EtOH, acetonitrile (MeCN), dimethylformamide (DMF), and ethyl acetate (EA). Its solubility was determined to be 6.75 mg in 100 mL of water at room temperature (25 °C), and even at 100 °C, its solubility is only 28.1 mg in 100 mL, which is significantly lower than those of ICM-102 and NTO (220 and 1600 mg in 100 mL of water at room temperature, respectively), , This low solubility may arise from the abundance of short intermolecular H-bonds. The same is true for compound 1b .…”
Section: Resultsmentioning
confidence: 98%
“…This process often causes the collapse of crystals, which interferes with highly dense packing, and gives rise to a low-energy density. NTO is strongly acidic (p K a = 3.67), which results in good solubility in aqueous solutions (160 g L –1 ) and can corrode metallic equipment during long-term storage . Therefore, in conclusion, an ideal insensitive high-energy molecule (IHEM) with promising applications should have not only a high density but also some notable drawbacks, such as complicated synthetic steps, strong acidity of resulting compounds, and the invariable presence of hydrates must be absent.…”
Section: Introductionmentioning
confidence: 99%
“…7), it can be seen that the highest increase in decolouration rate was observed at H2O2 concentration 65.29 mM. Increasing the H2O2 concentration above this value obviously does not increase the decolouration rate, on the contrary, the addition of 4 times higher dose hinders the reaction [31].…”
Section: Effect Of H2o2 Concentrationmentioning
confidence: 86%
“…Many chemical and biological processes have been investigated as potential treatment alternatives to GAC for munitions wastewater containing IM constituents [8,[12][13][14][15][16][17]. While some were able to remove one or two IMCs, none of them were effective in removing all IM compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaline hydrolysis of DNAN has been evaluated in laboratory treatability studies, but the process could not remove NTO [8]. Oxidative processes such as biological and chemical oxidation have been shown to remove DNAN and NTO [17,18], but they could not remove NQ [18]. Several studies showed microbial degradation of NTO, NQ, and DNAN, suggesting biological treatment may be a viable option [12,13,16,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%